IMPLEMENTATION OF THE TAHFIZ PROGRAM IN EARLY CHILDREN AT THE TAHFIDZ NAZRA CENDIKIA BARABAI HOUSE - Samsul Fajeri; Husin; Ma'rifah Shaleha; Abdul Rashid bin Abdul Aziz (International Forum of Researchers and Lecturers, 2022)
Education is learning and knowledge that is passed down from generation to generation through learning and training. One educational institution that is no less important to build is religion-based education, such as the Tahfidz Al-Qur'an Education institution. At this time the tahfidz program was very popular and respected by various institutions. This study aims to describe how the tahfidz program is implemented in early childhood at the Tahfidz Nazra Cendikia Barabai House. This research uses a descriptive qualitative research type. The results of the research show that the implementation of the tahfidz program at the Nazra Cendikia Hulu Sungai Tengah House consists of three main activities, namely planning, implementation and evaluation. The planning of the tahfidz program starts with discussions with the leaders and all tahfidz teachers. The implementation of the tahfidz program includes initial activities, namely greetings, prayers and reading blessings, followed by reading hypnotherapy, then murajaah together. The main activity is that the students give it to the teachers, before reading the memorized surah the child reads the Iqra or Al-Qur'an first. And finally the closing activity is the delivery of the surah that will be memorized next, murajaah memorization and reading prayers after learning. The assessments used are daily and semester assessments. The methods used are the makhraji, Jibril, ummi, and hypnotherapy methods. The main activity is that the students give it to the teachers, before reading the memorized surah the child reads the Iqra or Al-Qur'an first. And finally the closing activity is the delivery of the surah that will be memorized next, murajaah memorization and reading prayers after learning. The assessments used are daily and semester assessments. The methods used are the makhraji, Jibril, ummi, and hypnotherapy methods. The main activity is that the students give it to the teachers, before reading the memorized surah the child reads the Iqra or Al-Qur'an first. And finally the closing activity is the delivery of the surah that will be memorized next, murajaah memorization and reading prayers after learning. The assessments used are daily and semester assessments. The methods used are the makhraji, Jibril, ummi, and hypnotherapy methods